A Model for Ethics in Marketing - Bartels, Robert (Journal of Marketing, 1967)
Is a given marketing action always ethical, never ethical, or ethical relative to time, place, and circumstances? Upon what logical bases can a marketer determine what is “right” for him to do, not only in domestic but also in international business? This article presents a schematic plan for analyzing the variables inherent in the ethics of decision-making; and a framework for social and personal ethics is proposed.